Effects of Subchronic Exposure of Diclofenac on Growth, Histopathological Changes, and Oxidative Stress in Zebrafish (Danio rerio). (5th February 2014) - Praskova, Eva; Plhalova, Lucie; Chromcova, Lucie; Stepanova, Stanislava; Bedanova, Iveta; Blahova, Jana; Hostovsky, Martin; Skoric, Misa; Maršálek, Petr; Voslarova, Eva; Svobodova, Zdenka
Abstract : The aim of this study was to investigate effects of subchronic exposure to sublethal levels of diclofenac on growth, oxidative stress, and histopathological changes in Danio rerio . The juvenile growth tests were performed on Danio rerio according to OECD method number 215. Fish at the age of 20 days were exposed to the diclofenac environmental concentration commonly detected in the Czech rivers (0.02 mg L −1 ) and the range of sublethal concentrations of diclofenac (5, 15, 30, and 60 mg L −1 ) for 28 days. A significant decrease (P < 0.01 ) in the fish growth caused by diclofenac was observed in the concentrations of 30 and 60 mg L −1 . The identified value of LOEC (lowest observed effect concentration) was 15 mg L −1 of diclofenac and NOEC (no observed effect concentration) value was 5 mg L −1 of diclofenac. We did not find histopathological changes and changes of selected parameters of oxidative stress (glutathione S-transferase, glutathione reductase) in tested fish. The environmental concentration of diclofenac in Czech rivers did not have any effect on growth, selected oxidative stress parameters (glutathione S-transferase, glutathione reductase), or histopathological changes in Danio rerio but it could have an influence on lipid peroxidation.